Determinan Ekspor Komoditas Crude Palm Oil (CPO) Indonesia ke Kawasan Uni Eropa Periode 2013-2023 - Nadia Fazira; Putri Ayu (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2025)
This study aims to analyze the factors influencing Indonesia’s crude palm oil (CPO) exports to the European Union during the 2013–2023 period. The research gap arises because most previous studies focused primarily on price and exchange rate factors without considering the impact of the European Union’s environmental regulations on CPO trade. To address potential endogeneity in world CPO prices, this study employs the Instrumental Variable Two-Stage Least Squares (IV/2SLS) approach, using rapeseed oil prices as an instrument. The independent variables include world CPO prices, the Rupiah–US Dollar exchange rate, the European Union Industrial Production Index (IPI), and the Renewable Energy Directive II (RED II) policy. The results reveal that world CPO prices have a positive and significant effect on Indonesia’s CPO exports to the European Union, while the exchange rate and IPI have no significant impact. Meanwhile, the RED II policy has a significant negative effect, reducing Indonesia’s CPO export value by nearly 98% compared to the period before the policy implementation. This study contributes empirically to the international trade literature by demonstrating that the European Union’s renewable energy policy has transformed into a form of green protectionism. In practical terms, the findings highlight the importance of downstream industry development, export market diversification, and strengthening trade diplomacy as key strategies for Indonesia to adapt to increasingly stringent global environmental regulations.